Religiosity as Considered in Green Purchase Intention among Muslim Consumer - Al Hadi, M Qoshid; Budi, Iman Setya; Erziaty, Rozzana (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2024)
Introduction to The Problem: In recent years, Indonesia has shown strengthening figures in world sharia economic and financial reports. This encourages studies on Muslim consumer behavior more to sustainable. This article provides an overview of research on the behavior of Muslim consumers who are committed to environmental issues and have awareness of religion. Previous research has focused primarily on green consumer behavior, and reported mixed findings, depending on the knowledge background. Purpose/Objective Study: As an extension of previous research, this study will reveal the role of religiosity to impact green commitment (GC) and their purchasing intention. Design/Methodology/Approach: A total of 296 respondents' data was collected based on purposive sampling and analyzed through structural equation modeling (SEM) with SmartPLS version 3. Findings: The results show that religiosity influences GC and green purchase intention (GPI) as well as the role of GC to mediates the relationship between religiosity and GPI. Future research requires deeper investigation regarding the number and distribution of samples so that it can help better generalize the findings. Paper Type: Research Article Keywords: Religiosity; green commitment; green purchase intention; muslim consumer.